Mitochondrial Fatty Acid β-Oxidation Inhibition Promotes Glucose Utilization and Protein Deposition through Energy Homeostasis Remodeling in Fish. Issue 9 (7th July 2020) - Li, Ling-Yu; Li, Jia-Min; Ning, Li-Jun; Lu, Dong-Liang; Luo, Yuan; Ma, Qiang; Limbu, Samwel Mchele; Li, Dong-Liang; Chen, Li-Qiao; Lodhi, Irfan J; Degrace, Pascal; Zhang, Mei-Ling; et al.
ABSTRACT: Background: Fish cannot use carbohydrate efficiently and instead utilize protein for energy supply, thus limiting dietary protein storage. Protein deposition is dependent on protein turnover balance, which correlates tightly with cellular energy homeostasis. Mitochondrial fatty acid β-oxidation (FAO) plays a crucial role in energy metabolism. However, the effect of remodeled energy homeostasis caused by inhibited mitochondrial FAO on protein deposition in fish has not been intensively studied. Objectives: This study aimed to identify the regulatory role of mitochondrial FAO in energy homeostasis maintenance and protein deposition by studying lipid, glucose, and protein metabolism in fish. Methods: Carnitine-depleted male Nile tilapia (initial weight: 4.29 ± 0.12 g; 3 mo old) were established by feeding them with mildronate diets (1000 mg/kg/d) for 6 wk. Zebrafish deficient in the carnitine palmitoyltransferase 1b gene ( cpt1b ) were produced by using CRISPR/Cas9 gene-editing technology, and their males (154 ± 3.52 mg; 3 mo old) were used for experiments. Normal Nile tilapia and wildtype zebrafish were used as controls. We assessed nutrient metabolism and energy homeostasis–related biochemical and molecular parameters, and performed 14 C-labeled nutrient tracking and transcriptomic analyses. Results: The mitochondrial FAO decreased by 33.1–88.9% (liver) and 55.6–68.8% (muscle) in carnitine-depleted Nile tilapia and cpt1b -deficient zebrafish compared with their controls ( P < 0.05). Notably, glucose oxidation and muscle protein deposition increased by 20.5–24.4% and 6.40–8.54%, respectively, in the 2 fish models compared with their corresponding controls ( P < 0.05). Accordingly, the adenosine 5′-monophosphate–activated protein kinase/protein kinase B–mechanistic target of rapamycin (AMPK/AKT-mTOR) signaling was significantly activated in the 2 fish models with inhibited mitochondrial FAO ( P < 0.05). Conclusions: These data show that inhibited mitochondrial FAO in fish induces energy homeostasis remodeling and enhances glucose utilization and protein deposition. Therefore, fish with inhibited mitochondrial FAO could have high potential to utilize carbohydrate. Our results demonstrate a potentially new approach for increasing protein deposition through energy homeostasis regulation in cultured animals.